HIV Testing for Children in Resource-Limited Settings: What Are We Waiting For? - Kellerman, Scott (Public Library of Science, 2010)
Scott Kellerman and Shaffiq Essajee argue that the time has come to increase access to HIV testing for children, especially in sub-Saharan Africa.